RIP IT UP AND START AGAIN: REMIX AND CO-OPTION IN THE MEDIA INDUSTRY - Delfanti, Alessandro; Phan, Michelle (AoIR Selected Papers of Internet Research, 2021)
Media workers use radical remix techniques to produce content for the mainstream media industries. Rather than thinking of piracy as a form of resistance, we identify these practices of remix labor as a renewed commodification of media piracy and remix cultures (Johns 2009; Mueller 2019). Be it wanna-be influencers remaking the latest viral video on TikTok, videomakers producing dozens of rip-o-matic clips that will constitute the storyboard for TV ads, or writers churning out pieces in content farms in the hope they land on a newspaper, the media industry outsources work to and exploits masses of people who use piracy and remix to produce content based on scissor reels composed from existing audio, textual and visual materials.